Seismic vulnerability assessment of existing school buildings. (May 2021) - Domaneschi, Marco; Zamani Noori, Ali; Pietropinto, Maria Vittoria; Cimellaro, Gian Paolo
Highlights: Real-time data acquisition and structural health monitoring using wireless sensors. Use and comparison of different sensors (i.e. MEMS and force-balance units). Use of dynamic identification methods (i.e. output-only or forced-vibrations ones). Calibration of models to reproduce the actual dynamic response (adjacent buildings). Formulations to assess the seismic vulnerability of existing buildings. Abstract: This paper presents a methodology to perform the seismic vulnerability assessment of existing buildings. It starts with the acquisition of structural data from available construction drawings and field investigations to create a preliminary finite element model. Then, a wireless sensor network is used to collect the structural response at different locations. The sensors are connected and synchronized to each other to download and process data in real time. Modal identification methods, such as output-only and forced vibration techniques, are used to determine the modal characteristics and consequently calibrate the structural model for the subsequent vulnerability assessment. The proposed methodology is applied to a reinforced concrete school building in Italy. The seismic vulnerability is evaluated using a variety of alternative formulations. In particular, material nonlinearities and contact interaction at the structural joints are considered.